EVALUATION OF SELF COMPENSATING EMITTERS IRRIGATING WITH SALINE WATER: PART II: PROCESS CAPABILITY INDEX - Da Silva, Patricia F.; Neto, Jose Dantas; De Lima, Vera L. A.; Dos Santos, Delfran B.; Ribeiro, Pedro H. P. [UNESP] (Soc Brasil Engenharia Agricola, 2016)
The use of tools such as process capability index for irrigation aims to observe how this irrigation is adequate in terms of quality. The aim of the study was analyzing the Christiansen uniformity coefficient and the flow of a drip irrigation system with self-compensating emitters under water different salt concentrations, using the process capability index. The research was conducted in a greenhouse at the Federal University of Campina Grande (UFCG). The experimental design was a randomized block in a factorial 5 x 2 with three replications, the factors consisted of five levels of irrigation water salinity (CEw) (0.6, 1.5, 2.5, 3.5 and 4.5 dS m(-1) at 25 degrees C) and two running times (0 and 350 hours of operation). The Christiansen uniformity coefficient (CUC) for new and used emitters was greater than 90%, in different salt concentrations studied. The flow of emitters is maintained within the statistical quality control, since management and maintenance operations are made after 350 hours of operation. The potential process capability index for the Christiansen uniformity coefficient was higher than recommended for new and used emitters, being the process within the required specifications.
Keywords: quality engineering; flow; quality control; Christiansen uniformity